The History of Chinese Civilization
IX, 187 p. 36 illus., 28 illus. in color.
Keywords: This book tracks the entire history of Chinese civilization from a broad historical view. Its narrative spans a long period between primitive society and contemporary civilization, which makes it a unique academic works. From an academic point of view, this book is accurate in history and combines historical theories. Although brief, it captures the main thrust of the development of Chinese civilization and achieves a broad outline. Important figures, historical events, and achievements of civilization in all times are involved and discussed. From a theoretical point of view, based on the characteristics of early Chinese civilization, the book discusses the connotation of key concepts such as "civilization" and "Chinese civilization", which have certain theoretical value. From a contemporary and practical perspective, the book helps readers understand the history of Chinese civilization and promotes cultural exchanges between China and the world and leads to a better understanding of today’s China.